1997
DOI: 10.1007/bf03012773
|View full text |Cite
|
Sign up to set email alerts
|

Rocuronium prevents succinylcholine-induced fasciculations

Abstract: F. Donati PhD MD FRCFCP~'po~: The aim of this study was to assess the effect of rocuronium pretreab-,ent at 3 and 1.5 min before sucdnytcholine administration on fasdculations, neuromuscular blockade and intubating conditions.Methods: Sixty ASA I or II adults scheduled for elective surgery were anae~etised with midazolam, fentanyl, propofol, N20 and isoflurane. They were randomised in a double blind manner into three groups: group ROC-3 rain (n = 22) received 0.05 mg'kg -I rocuronium, 3 min before 2 rng-kg -I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
0
8
0
4
Order By: Relevance
“…Succinylcholin · Cisatracurium · Nebenwirkungen · Faszikulationen · Myalgien Dank seines unerreichten Wirkprofils (rascher Wirkungseintritt, sehr kurze Wirkungsdauer) ist Succinylcholin nach wie vor klinisch bedeutsam [3,6,7,8,9,13]. Dennoch hat Succinylcholin relevante Nebenwirkungen; dazu gehören Faszikulationen und postoperative Myalgien [3,5,6,15,24].…”
Section: Schlüsselwörterunclassified
See 3 more Smart Citations
“…Succinylcholin · Cisatracurium · Nebenwirkungen · Faszikulationen · Myalgien Dank seines unerreichten Wirkprofils (rascher Wirkungseintritt, sehr kurze Wirkungsdauer) ist Succinylcholin nach wie vor klinisch bedeutsam [3,6,7,8,9,13]. Dennoch hat Succinylcholin relevante Nebenwirkungen; dazu gehören Faszikulationen und postoperative Myalgien [3,5,6,15,24].…”
Section: Schlüsselwörterunclassified
“…Verglichen mit einer TOF-Ratio >0,9 (gleichbedeutend mit einer ausreichenden neuromuskulären Funktion der Larynx-und Pharynxmuskulatur) waren die Schutzreflexe (Schluckmechanismus, Freihalten der Atemwege) bei Probanden mit einer TOF-Ratio unter 0,9 mit einer 4-bis 5fach höheren Inzidenz eingeschränkt [21]. Über das optimale Präkurarisie-rungsintervall, d. h. das Intervall zwischen dem nichtdepolarisierenden Muskelrelaxans und Succinylcholin herrscht Unklarheit in der vorhandenen Literatur [6,13,16]; allerdings scheint ein längeres Intervall die Effektivität der Präkurari-sierung zu verbessern [3,6,16]. Die neuromuskuläre Potenz von Cisatracurium beträgt annähernd das 4Fache von Atra- curium, entsprechend der ED 95 von 0,05 mg/kg für Cisatracurium und 0,2-0,25 mg/kg für Atracurium [19].…”
Section: Introductionunclassified
See 2 more Smart Citations
“…The theoretical calculation using published pharmacodynamic and pharmacokinetic data showed that a dose of rocuronium equivalent to 10% of the ED 95 (ED 95 = 0.3 mg/kg) would rarely produce a measurable neuromuscular effect and should be therefore recommended as an appropriate dose for precurarization [10]. However, in previous studies [5,[11][12][13], 20-30% of the ED 95 of rocuronium was generally used for precurarization, and effectiveness for defasciculation was examined. Although it is anticipated that a larger dose of rocuronium can greatly suppress suxamethonium-induced fasciculation, the risk of a significant neuromuscular block in several minutes after the precurarization dosing may become greater.…”
Section: Introductionmentioning
confidence: 99%